A negotiation based dynamic pricing heuristic in cloud computing. (2018) - Baranwal, Gaurav; Kumar, Dinesh; Raza, Zahid; Vidyarthi, Deo Prakash
Over the years, cloud computing has emerged as a good business platform for IT related services. In cloud, prices of computing resource act as lever to control the utilisation of the resources. That is the reason, when the number of cloud customers started increasing, cloud service providers started offering resources with various pricing schemes to attract customers. This work proposes a negotiation based heuristic for dynamic pricing that considers behaviour of both the service provider and the customer and tries to optimally satisfy both for pricing. Both customer and provider are reluctant to reveal information about their utility to each other. The designed utility function for provider considers payment offered by customer and opinion of the provider about customer. Similarly, utility function for customer considers price offered by the provider and opinion of customer about provider. This will encourage both to offer their true value. Performance study indicates that the proposed method performs well and is a potential candidate for its implementation in a real cloud.